2020
DOI: 10.3390/cancers12071848
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Assessment of Patients with Lynch Syndrome and Sarcomas Underpinning the Association with MSH2 Germline Pathogenic Variants

Abstract: Lynch syndrome (LS) is a hereditary cancer-predisposing syndrome associated most frequently with epithelial tumors, particularly colorectal (CRC) and endometrial carcinomas (EC). The aim of this study was to investigate the relationship between sarcomas and LS by performing clinical and molecular characterization of patients presenting co-occurrence of sarcomas and tumors from the LS spectrum. We identified 27 patients diagnosed with CRC, EC, and other LS-associated tumors who had sarcomas in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…Undifferentiated pleomorphic/unclassifiable sarcoma accounted for eight cases and in one cases the subtype was not specified. 4 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 While most studies referred to case reports or case series, Doyle and colleagues investigated the frequency of MMR deficiency in a cohort of 279 cases and identified 6 MMR deficient cases (2%). 26 In all these studies, seventeen patients had a germline mutation in one of the mismatch repair genes (Lynch syndrome n = 13; Muir‐Torre syndrome n = 2; Constitutional Mismatch Repair Deficiency n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Undifferentiated pleomorphic/unclassifiable sarcoma accounted for eight cases and in one cases the subtype was not specified. 4 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 While most studies referred to case reports or case series, Doyle and colleagues investigated the frequency of MMR deficiency in a cohort of 279 cases and identified 6 MMR deficient cases (2%). 26 In all these studies, seventeen patients had a germline mutation in one of the mismatch repair genes (Lynch syndrome n = 13; Muir‐Torre syndrome n = 2; Constitutional Mismatch Repair Deficiency n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Sporadic sarcomas are rarely associated with microsatellite instability. However, a Brazilian study recently indicated that sarcomas, although rare, are linked to the Lynch syndrome spectrum of tumours [28,29]. An increased lifetime incidence is reported; but the exact risk for sarcoma development has not been fully elucidated [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that defects in DNA mismatch repair (Lynch syndrome) predispose to colon and other cancers. The new study found that the condition can also lie in the etiology of sarcomas [ 7 ]. Fanconi anemia is connected to the defects of machinery dealing with the aberrant replication of damaged DNA with inter-strand DNA crosslinks.…”
mentioning
confidence: 99%
“…in the etiology of sarcomas [7]. Fanconi anemia is connected to the defects of machinery dealing with the aberrant replication of damaged DNA with inter-strand DNA crosslinks.…”
mentioning
confidence: 99%